Early-Life Human Microbiota Associated With Childhood Allergy Promotes the T Helper 17 Axis in Mice - Petursdottir, Dagbjort H.; Nordlander, Sofia; Qazi, Khaleda Rahman; Carvalho-Queiroz, Claudia; Ahmed Osman, Omneya; Hell, Eva; Björkander, Sophia; Haileselassie, Yeneneh; Navis, Marit; Kokkinou, Efthymia; Lio, Ivan Zong Long; Hennemann, Julia; et al. (Frontiers in Immunology, 2017)
The intestinal microbiota influences immune maturation during childhood, and is implicated in early-life allergy development. However, to directly study intestinal microbes and gut immune responses in infants is difficult. To investigate how different types of early-life gut microbiota affect immune development, we collected fecal samples from children with different allergic heredity and inoculated germ-free mice. Immune responses and microbiota composition were evaluated in the offspring of these mice. Microbial composition in the small intestine, the caecum and the colon was determined by 16S rRNA sequencing. The intestinal microbiota differed markedly between the groups of mice, but only exposure to microbiota associated with allergic heredity and known future allergy in children resulted in a T helper 17 (Th17)-signature, both systemically and in the gut mucosa in the mouse offspring. These Th17 responses could be signs of a particular microbiota and a shift in immune development, ultimately resulting in an increased risk of allergy.